Optimal Management of the Public and Patients by Pharmacists in the Era of COVID-19: An Evidence-Based Review and Practical Recommendations - Song, Zaiwei; Hu, Yang; Ren, Zhenyu; Wang, Guanru; Liu, Shuang; Zheng, Siqian; Yang, Li; Zhao, Rongsheng (Frontiers in Public Health, 2022)
Purpose: Currently, managing the public and patients during the COVID-19 pandemic is constituting a health care challenge worldwide. Patient-oriented management is of crucial importance to promote emergency preparedness and response. This study aims to formulate an integrated pharmacist management strategy of the public and patients and to provide evidence-based and practical references. Methods: Evidence-based review and practical analysis were utilized. First, PubMed, EMBASE and Chinese database were searched. Studies about patient management in major public health emergencies were included. Second, the Chinese experience of patient management was analyzed and identified. Finally, combining evidence-based and practical analysis, the pharmacist management strategy of the public and patients was researched and summarized. Results: Regarding the home quarantine period, pharmacist management services should include medication guidance, guidance on risk monitoring, sanitation measures education, health management guidance and psychological support. Regarding the outpatient visit period, pharmacists should participate in the control of in-hospital infections and provide physician-pharmacist joint clinic services, pharmacy clinic services, medication therapy management, medication consultation services, drug supply guarantee and drug dispensing services. Regarding the hospitalization period, pharmacist management services should include monitoring and evaluating the safety and efficacy of medications, providing strengthened care for special populations and other pharmaceutical care. For non-hospitalized or discharged patients, pharmacist management services should include formulating medication materials and establishing pharmacy management files for discharged patients. Conclusion: An evidence-based, patient-centered and entire-process-integrated pharmacist management strategy of the public and patients is established, which remedies the gaps in the existing patient management and can be implemented to support pharmacists' contributions to COVID-19 pandemic control.